2021
DOI: 10.1186/s12872-021-02046-x
|View full text |Cite
|
Sign up to set email alerts
|

Natural history and prognostic implications of left ventricular end-diastolic pressure in reperfused ST-segment elevation myocardial infarction: an analysis of the thrombolysis in myocardial infarction (TIMI) II randomized controlled trial

Abstract: Background The aim of the current study is to assess the natural history and prognostic value of elevated left ventricular end-diastolic pressure (LVEDP) in patients with ST-segment elevation myocardial infarction (STEMI) after reperfusion with thrombolysis; we utilize data from the Thrombolysis in Myocardial Infarction (TIMI) II study. Methods A total of 3339 patients were randomized to either an invasive (n = 1681) or a conservative (n = 1658) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Similar to our result, Tesak et al [20] showed statistically significant higher LVEDP in non-survivors group (median= 30 mmHg, range 22-39 mmHg) when compared to survivors group (24 mmHg, range 12-38 mmHg) with p-value= 0.001 & with LVEDP was independent predictor for 30-day mortality [AUC 0.715, 95% CI (0.626; 0.803), p-value <0.001, cut-off value ≥20.5 mmHg]. Also, Khan et al [21] in examination of the TIMI II randomised controlled trial examining the prognostic significance of LVEDP in re-perfused STEMI, as well as its natural history. That study subdivided patients into 4 quartiles according to their LVEDP (quartile 1: median LVEDP= 10 mmHg vs 16 mmHg in quartile 2, 20 mmHg in quartile 3 and 27 mmHg in quartile 4) and found significant increase of all-cause mortality [15 patients (5%), 17 patients (5%), 15 patients (6%) and 39 patients (14%); respectively] and heart failure [41 patients (12%) vs. 51 patients (15%), 54 patients (21%) and 86 patients (32%); respectively] with p-value < 0.001.…”
Section: Discussionmentioning
confidence: 92%
“…Similar to our result, Tesak et al [20] showed statistically significant higher LVEDP in non-survivors group (median= 30 mmHg, range 22-39 mmHg) when compared to survivors group (24 mmHg, range 12-38 mmHg) with p-value= 0.001 & with LVEDP was independent predictor for 30-day mortality [AUC 0.715, 95% CI (0.626; 0.803), p-value <0.001, cut-off value ≥20.5 mmHg]. Also, Khan et al [21] in examination of the TIMI II randomised controlled trial examining the prognostic significance of LVEDP in re-perfused STEMI, as well as its natural history. That study subdivided patients into 4 quartiles according to their LVEDP (quartile 1: median LVEDP= 10 mmHg vs 16 mmHg in quartile 2, 20 mmHg in quartile 3 and 27 mmHg in quartile 4) and found significant increase of all-cause mortality [15 patients (5%), 17 patients (5%), 15 patients (6%) and 39 patients (14%); respectively] and heart failure [41 patients (12%) vs. 51 patients (15%), 54 patients (21%) and 86 patients (32%); respectively] with p-value < 0.001.…”
Section: Discussionmentioning
confidence: 92%
“…When using only the systolic support, a further increase in the support pressure would theoretically lead to the desired EF. However, the EDP would remain elevated, which has been identified as a potential predictor of heart failure ( 44 46 ). Whether solely the reduction in EDP would eventually lower the risk needs to be investigated further.…”
Section: Discussionmentioning
confidence: 99%